(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت الدراسة إلى التعرف على العلاقة بين خروج المرأة للعمل وبين توافقها الزواجي لدى عينة من النساء المتزوجات في محافظة اللاذقية، من العاملات وغير العاملات في القطاعين الحكومي والخاص، وتكونت عينة الدراسة من (200) أمرأة (106 من العاملات و94 من غير العاملات) واستخدمت الباحثة لانجاز الدراسة مقياس التوافق الزواجي من إعداد الباحثة. وتوصلت الدراسة إلى وجود فروق دالة إحصائياً بين متوسط درجات النساء العاملات ومتوسط درجات النساء غير العاملات في توافقهن الزواجي الكلي، وكذلك وجود فروق دالة إحصائياً بين متوسط النساء العاملات في القطاع الحكومي وبين متوسط النساء العاملات في القطاع الخاص في توافقهن الزواجي، ولصالح العاملات في القطاع الحكومي. This research’s main Aim was To Identify The relation between woman employment with her marital adjustment within A Sample Of Wives In Lattakia, Syria. The sample Consisted Of (200) Wives ( 106 employment w0men and 94 unemployment women) To achieve her study, researcher has been used Measure of: " Marital Adjustment " Prepared by Researcher. The research results were: - There are a differences of statistical significance in marital adjustment between employment and un employment women. - There are a differences of statistical significance in marital adjustment of employment women according to work sector (governmental, private ) .